Acute and 3-month effects of calcium carbonate on the calcification propensity of serum and regulators of vascular calcification: secondary analysis of a randomized controlled trial. Issue 3 (March 2016) - Bristow, S.; Gamble, G.; Pasch, A.; O'Neill, W.; Stewart, A.; Horne, A.; Reid, I.
Abstract Summary Calcium supplements have been associated with increased cardiovascular risk, but the mechanism is unknown. We investigated the effects of calcium supplements on the propensity of serum to calcify, based on the transition time of primary to secondary calciprotein particles (T50 ). Changes in serum calcium were related to changes in T50 . Introduction Calcium supplements have been associated with increased cardiovascular risk; however, it is unknown whether this is related to an increase in vascular calcification. Methods We investigated the acute and 3-month effects of calcium supplements on the propensity of serum to calcify, based on the transition time of primary to secondary calciprotein particles (T50 ), and on three possible regulators of calcification: fetuin-A, pyrophosphate and fibroblast growth factor-23 (FGF23). We randomized 41 postmenopausal women to 1 g/day of calcium as carbonate, or to a placebo containing no calcium. Measurements were performed at baseline and then 4 and 8 h after their first dose, and after 3 months of supplementation. Fetuin-A, pyrophosphate and FGF23 were measured in the first 10 participants allocated to calcium carbonate and placebo who completed the study. Results T50 declined in both groups, the changes tending to be greater in the calcium group. Pyrophosphate declined from baseline in the placebo group at 4 h and was different from the calcium group at this time point (p = 0.04). There were no other significant between-groups differences. The changes in serum total calcium from baseline were significantly related to changes in T50 at 4 h (r = −0.32, p = 0.05) and 8 h (r = −0.39, p = 0.01), to fetuin-A at 3 months (r = 0.57, p = 0.01) and to pyrophosphate at 4 h (r = 0.61, p = 0.02). Conclusions These correlative findings suggest that serum calcium concentrations modulate the propensity of serum to calcify (T50 ), and possibly produce counter-regulatory changes in pyrophosphate and fetuin-A. This provides a possible mechanism by which calcium supplements might influence vascular calcification.